2024
DOI: 10.1371/journal.pone.0301417
|View full text |Cite
|
Sign up to set email alerts
|

Exploring knowledge, attitudes and practice toward medication therapy management services among pharmacists in Yemen

Najmaddin A. H. Hatem,
Mohamed Izham Mohamed Ibrahim,
Seena A. Yousuf

Abstract: Medication therapy management (MTM) refers to the activities provided by pharmacists that patients recognize as evidence of care being provided. It encompasses the services that patients value and consider valuable. Many developing nations like Yemen have had poor implementation of MTM services. Thus, this research assessed the Knowledge, Attitudes, and Practices (KAP) of Yemen pharmacists regarding MTM. We conducted a cross-sectional study using a self-administered questionnaire among pharmacists in Sana’a, Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Furthermore, a recent study in Yemen showed that only 11% of sampled pharmacists frequently offered medication therapy management MTM services, and formulating a medication treatment plan received the least MTM service among them. 29 Therefore, implementing clinical pharmacy services necessitates the integration of a new cross-disciplinary collaboration model where pharmacists engage in clinical decision-making, as well as the introduction of a new profession into the provision of healthcare. Additionally, in different parts of the world where CPSs are being implemented for the first time in the nation’s health system, new care models and the measures that correlate with them should be used.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study in Yemen showed that only 11% of sampled pharmacists frequently offered medication therapy management MTM services, and formulating a medication treatment plan received the least MTM service among them. 29 Therefore, implementing clinical pharmacy services necessitates the integration of a new cross-disciplinary collaboration model where pharmacists engage in clinical decision-making, as well as the introduction of a new profession into the provision of healthcare. Additionally, in different parts of the world where CPSs are being implemented for the first time in the nation’s health system, new care models and the measures that correlate with them should be used.…”
Section: Discussionmentioning
confidence: 99%